The time course of recovery from a mesocycle of periodized plyometric training - Ebben, W.; Fauth, M.; VanderZanden, T.; Petushek, E.; Feldmann, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study evaluated the effectiveness of a mesocycle of periodized plyometric training and the influence of the duration of the post training recovery period. All subjects' countermovement jump height, peak power, and body mass were assessed with a force platform prior to and 2, 4, 6, 8, and 10 days after training. Jump height was 25.0% greater (p = 0.05) after training with no difference (p > 0.05) between the recovery periods of 2, 4, 6, 8, or 10 days. Peak power was 11.6 to 14.3 % greater (p = 0.001) after training for the training group with no difference (p > 0.05) between recovery periods of 2, 4, 6, 8, or 10 days. Periodized plyometric programs with decreasing volume and increasing intensity improve jump performance without a need for a post training recovery period.